Transcatheter closure of patent ductus arteriosus with the new Amplatzer Duct OccluderII - Ji, Wei (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2013)
OBJECTIVE: To evaluate the indications, methodology and results of the transcatheter closure of patent ductus arteriosus (PDA) with the new Amplatzer Duct Occluder II (ADO-II)